Data Monetization as a New Economic Asset in the Digital Economy Ecosystem - Salamah Utami (PT. AVID MEDIA INDONESIA, 2026)
The rapid development of the digital economy has transformed data from a by-product of digital activities into a strategic economic asset that can be monetized and utilized to create new sources of value. This study aims to analyze data monetization as a new economic asset within the digital economy ecosystem by examining its value creation mechanisms, monetization pathways, and governance challenges. This research employs a qualitative approach with a descriptive-analytical design based on a systematic literature review of scholarly articles published between 2020 and 2025. Data were collected through documentation techniques from reputable journals and analyzed using qualitative content analysis, thematic categorization, and conceptual synthesis. The findings reveal that data generates economic value through three main pathways: operational efficiency, direct data commercialization, and data-driven services. Advanced technologies such as artificial intelligence, big data analytics, and IoT play a crucial role in enabling these processes. However, the study also identifies significant challenges, including unequal value distribution, platform dominance, and concerns related to data privacy and governance. The discussion highlights the need for inclusive and transparent frameworks to ensure fair participation in the data economy. In conclusion, data monetization represents a transformative force in the digital economy, requiring integrated strategies that combine technological innovation with ethical governance to achieve sustainable and equitable economic outcomes.